RI 5532 Nickel-Cobalt-Iron-Bearing Deposits In Puerto Rico ? Introduction And Summary - W. L. Heidenreich (The National Institute for Occupational Safety and Health (NIOSH), 1959)
This report describes the methods and results of field investigations conducted by the Bureau of Mines between December 1956 and December 1957 on seven deposits of nickel-cobalt-iron-bearing laterite and weathered serpentine near the west coast of Puerto Rico east and south of Mayaguez. These deposits were named, for purposes of identification, Guanajibo, Punta Guanajibo, Las Mesas, north and south deposits of the Rosario Southeast group, and the west and east deposits of the Maricao Southwest group. In addition, the lower 17 miles of the Guanajibo River Valley was tested at widely spaced intervals for possible concentrations of magnetite and chromite in the alluvial sands. The objective of the investigations was to appraise, by drilling and sampling, the two largest deposits--the Guanajibo and Las Mesas. Testing of the smaller deposits was much more restricted. Field investigations consisted of mapping, drilling with power auger, sampling drill-hole sections, and pre-paring samples for chemical analyses, mineralogical studies, and metallurgical tests. The work was financed jointly under a cooperative agreement by the Bureau of Mines and the Economic Development Administration, an agency of the Puerto Rican Commonwealth.